Transcriptome sequencing revealed that lymph node metastasis of papillary thyroid microcarcinoma is associated with high THBS4 expression and PDGFRA+ cancer-associated fibroblasts - Hu, LeYin; Lin, Yi; Zheng, JingYu; Wan, Li; Zhao, Rui; Ma, Yi; Li, JianMin (Frontiers in Oncology, 2025)
BackgroundCervical lymph node metastasis is a major factor influencing recurrence after surgery for papillary thyroid cancer. Molecular markers that can predict the presence of lymph node metastasis and assess the aggressiveness of papillary thyroid microcarcinoma (PTMC) remain poorly understood. The research question addressed whether specific genes, such as thrombospondin-4 (THBS4), could serve as predictive biomarkers for guiding surgical strategies, particularly in cases where current imaging modalities fail to detect LNM in the central region, and the decision for prophylactic central neck dissection remains controversial.MethodsTranscriptome sequencing was employed to screen for differentially expressed genes and perform enrichment analysis. The study defined two groups of PTMC patients: LNM(n=50) and NLNM(n=50). 10 samples from each group were used for transcriptome sequencing. The expression of THBS4 was evaluated in both groups. Additionally, the correlation between THBS4 expression and cancer-associated fibroblasts (CAFs), specifically the PDGFRA+ inflammatory CAFs, was investigated to understand the stromal regulatory protein’s role in PTMC aggressiveness.ResultsThe analysis of sequencing data revealed that THBS4 expression was significantly higher in LNM PTMC compared to the NLNM group (Fold Change > 1.6 and P < 0.05). LNM PTMCs were also associated with a higher presence of PDGFRA+ inflammatory CAFs (P < 0.05), while no significant difference in the quantity of SMA+ myofibroblastic CAFs was observed between the two groups(P>0.05). Immunohistochemical analysis demonstrated increased THBS4(P < 0.01) and PDGFRA(P < 0.001) expression in LNM groups, while SMA staining showed no significant intergroup differences(P>0.05).ConclusionThis study’s findings indicate that THBS4 could be a potential biomarker for predicting the risk of lymph node metastasis in papillary thyroid microcarcinoma, thus potentially guiding more personalized surgical interventions. Further validation in larger patient cohorts and the interactions between THBS4 and CAFs are necessary.